Studing the Impact of Outlets Interior design on Hotel Customers Flow - Sally Fathi El-Saied Abdelaal (2013)
arabic Summary .
reference (323-335).
Ph in hotel Management
Faculty of Tourism and Hotel : Helwan University .
Keywords: Resort Hotels .